Experimental analysis on ballistic performance of newly developed sandwich hybrid natural composites. (2020) - Kumar, G. Arun; Kumar, M. Ranjith; Babu, A.M. Ramesh; Kumar, R. Ram; Kumar, G. Sathish; Parameswaran, P.
Abstract: The hybrid composites was prepared from epoxy polymer layers with aluminum sheets of 1 and 2 layers. The epoxy polymer was mixed with conch sea shells (sharp parts) in order to gain more impact strength and incorporated with chopped banana fibers. The mechanical properties such as flexural, tensile, hardness tests were carried out along with the ballistic test. The microstructure SEM images showed bonding of banana fiber along with the banana fibers. Ballistic test with the short hand gun, and the conclusion made the composite fits for ballistic protection.